Influence of Rice Husk Ash on the Properties of Concrete (Journal of Environmental Science and Natural Resources, 2016)
This research was carried out to investigate various physical properties of Rice Husk Ash (RHA) and, some physical and mechanical properties of concrete incorporating RHA in different proportions. The concrete specimens were tested at 7, 21 and 28 days after curing. Test results revealed that the specific gravity of RHA was found lower than that of sand. The density of concrete containing RHA was recorded between 80-110 lb.ft-3, which is lower than conventional concrete. Water absorption was found increasing with the increase of RHA content in concrete specimens. There were significant variations in compressive strength values of concrete containing 5%, 10% and 20% volume of RHA. The compressive strength of 5% RHA specimen was 150-200% higher than that of other specimens. Hence, upto 5% replacement of RHA could be recommended for making normal lightweight concrete. The splitting tensile strength was about 9-10% of compressive strength. It was concluded that upto 5% RHA can be used effectively in making normal lightweight concrete. The higher percentage of RHA could be used in making non-structural concrete where the strength of concrete is not concerned.J. Environ. Sci. & Natural Resources, 9(1): 29-33 2016